Cultivating Graduate STEM Pathways: How Alliance-Based STEM Enrichment Programs Broker Opportunity for Students of Color - Garcia, Ariana L.; Lane, Tonisha B.; Rincón, Blanca E. (Frontiers in Education, 2021)
To understand how higher education institutions broker graduate opportunities for Students of Color (SOCs) in STEM, we employ a single case study of a Louis Stokes Alliance for Minority Participation (LSAMP) alliance. Drawing primarily from student interviews and informed by Small’s (2006) organizational brokerage theory, our findings illuminate how (1) alliance-based STEM enrichment programs (SEPs) bridge social capital via interorganizational networks and (2) how SEP instability creates barriers to building the trust that is central to the brokerage process. We conclude with recommendations for future research and practice.